THE IMPORTANCE OF LAND BANK FOR AGRICULTURAL DEVELOPMENT AND THE TECHNIQUE OF GRANTING RURAL LAND LOAN - LUCIAN-ION MEDAR; IRINA-ELENA CHIRTOC (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2013)
In Romania, with the liberalization of the land market, appears the prospect of functioning of aspecialized agricultural bank which might be named ,,land bank’’. In principle, this institution can buy and sellagricultural land and to provide priority "rural land loan" for farm development. Mainly, it may incorporate anadvantageous loan system created for those who want to buy land for agriculture use, once of the liberalizationof land market since 2014. In this article we present some details about importance of this credit institution andgrant technique of rural land loan . Currently, the number of Romanian farmers grouped in associations is verysmall compared to the millions agricultural holdings. Young farm development can be possible only byappealing to an "engine" type "rural land loans" and which may more quickly solve their financial problems.